ETR 300 : Dezia Photo Enterprise Photo Shop / Norita Ibrahim ...[et al.] - Ibrahim, Norita; Abd Rahim, Rusbaizura; Mahayudin, Mohd Hidzir; Mohd Khairy, Ermawaty; Nazeli, Norazlina (2000)
The name of our business is Dezia Photo Enterprise which provide develop photo service at Bandar Aman Jaya. Other than that, we also sell photography equipment such as camera, film and battery. We decide to involve in this business because there is no photo shop run by Bumiputera at Bandar Aman Jaya. Besides, we chose this business because of increase of demand for photo especially during festival and marriage season and for passport photo. Our target customer in that area is student from Aman Jaya College and UUM Sungai Petani Branch. 5 entrepreneurs who try to break off the monopoly that control by Chinese before run this business. Capital to start our business is RM 100,000 and RM 80,000 is loan from Bumiputera Commerce Bank.